Oxidative Wear in Lubricated Contact - Newley,RA; Spikes,HA; Macpherson,PB (Journal of Lubrication Technology, 1980)
Lubricant antioxidant additives are known to reduce fretting wear. Wear tests have been carried out in association with chemical analyses of the test lubricant to elucidate the mechanism of oxidative wear. It is shown that the rate of wear is not directly related to the concentration in the lubricant of either acids or peroxides. It is proposed that the metal is oxidized by reacting with peroxy radicals which form as intermediates as the lubricant is oxidized. The reduction of wear in the presence of antioxidants is a result of the elimination of these radicals by the additive.